Statistics for research : with a guide to SPSS - Argyrous, George (Los Angeles : SAGE, 2011)
This fully updated edition of Statistics for Research provides a comprehensive introduction to statistics with a guide to SPSS. It explains statistical concepts in a straightforward and accessible way using practical examples from a variety of disciplines.
Previous ed.: 2005.
Includes index.
rua 28/11/13
Loans
Keywords: Social sciences; Statistics; Research - statistics; SPSS